An annotated checklist of the fish fauna of the river systems draining the Kahuzi‐Biega National Park (Upper Congo: Eastern DR Congo). Issue 3 (23rd February 2020) - Kisekelwa, Tchalondawa; Snoeks, Jos; Vreven, Emmanuel
Abstract: The Kahuzi‐Biega National Park (KBNP), situated mainly in the Eastern Highlands Ecoregion of the Upper Congo basin, is drained by the Lowa and Ulindi rivers, and some western affluents of Lake Kivu. In this study, the first list of the fish diversity of these systems is provided based on museum collections and complemented, for the Lowa River system and the western Lake Kivu affluents, with recently collected specimens (2013–2017). A total of 118 species are reported from the Lowa basin, 22 from the Ulindi basin and seven from these Lake Kivu affluents. Within the Lowa and Ulindi, respectively, five and one species, all cichlids, have been introduced. Currently, 51 species are reported from within the park, only two of which have been reported from the highlands, i.e., Amphilius kivuensis from the Luha, the source of the Luka River, and Clarias liocephalus from the headwaters of the Lake Kivu' affluents. With a total of 30 species, Cyprinidae is by far the largest family, representing 25% of the total species diversity of the Lowa basin. It is followed by Mormyridae with 13 species (11%), Alestidae and Mochokidae with 10 species each (8%), Clariidae and Amphiliidae with eight species (7%), and Distichodontidae with six species (5%). Seven new species for science were discovered and 11 species were found to be endemic to the Lowa system. Although further exploration is needed, this underscores the importance of the KBNP in protecting the fish fauna of the Lowa basin but also highlights the park's limited coverage of the fish fauna of the Lowa basin.